The Relationship Between High School Student's Self-Confidence and Speaking Performance - Fadilah, Ika Nur; Dyah Aminatun (LPPM Universitas PGRI Semarang, 2025)
This study aims to examine the correlation between students' self-confidence and speaking performance at SMAN 1 Candipuro. The researchers employed a quantitative research design. The sample for this research consists of students from classes XI F3 and XI F4.The sample of this study was 69 of those students. The researchers used the students' speaking test scores as the main indicator to classify them as samples for this research. To collect data, the researchers used two research instruments: a speaking test and questionnaires. The speaking test was used to measure the students' speaking abilities, the questionnaires measured their levels of self-confidence. The results of the correlation analysis showed that there is significant correlation between students' self-confidence and their speaking performance at SMAN 1 Candipuro. This is supported by a p-value of 0.392 which is lower than the alpha level of 0.753. Based on the result, it was shown that 0.392 was in interval low correlation between self-confidence and English-speaking skill. Higher self-confidence is associated with better speaking abilities. This suggests that enhancing students' self-confidence can improve their speaking skills